In vivo quantitative mapping of human mitochondrial cardiac membrane potential: a feasibility study - Pelletier-Galarneau, Matthieu; Petibon, Yoann; Ma, Chao; Han, Paul; Kim, Sally Ji Who; Detmer, Felicitas J.; Yokell, Daniel; Guehl, Nicolas; Normandin, Marc; El Fakhri, Georges; Alpert, Nathaniel M. (European journal of nuclear medicine and molecular imaging, 2021)
Purpose Alteration in mitochondrial membrane potential (ΔΨ m ) is an important feature of many pathologic processes, including heart failure, cardiotoxicity, ventricular arrhythmia, and myocardial hypertrophy. We present the first in vivo, non-invasive, assessment of regional ΔΨ m in the myocardium of normal human subjects. Methods Thirteen healthy subjects were imaged using [ 18 F]-triphenylphosphonium ([ 18 F]TPP+) on a PET/MR scanner. The imaging protocol consisted of a bolus injection of 300 MBq followed by a 120-min infusion of 0.6 MBq/min. A 60 min, dynamic PET acquisition was started 1 h after bolus injection. The extracellular space fraction (f ECS ) was simultaneously measured using MR T1-mapping images acquired at baseline and 15 min after gadolinium injection with correction for the subject’s hematocrit level. Serial venous blood samples were obtained to calculate the plasma tracer concentration. The tissue membrane potential (ΔΨ T ), a proxy of ΔΨ m , was calculated from the myocardial tracer concentration at secular equilibrium, blood concentration, and fECS measurements using a model based on the Nernst equation. Results In 13 healthy subjects, average tissue membrane potential (ΔΨ T ), representing the sum of cellular membrane potential (ΔΨ c ) and ΔΨ m , was − 160.7 ± 3.7 mV, in excellent agreement with previous in vitro assessment. Conclusion In vivo quantification of the mitochondrial function has the potential to provide new diagnostic and prognostic information for several cardiac diseases as well as allowing therapy monitoring. This feasibility study lays the foundation for further investigations to assess these potential roles. Clinical trial identifier: NCT03265431